Mobile application for early detection of non-communicable diseases - Kurniasih, Hesti; Widyawati, Melyana Nurul; Kurnianingsih, Kurnianingsih (Universitas Muhammadiyah Purwokerto, 2022)
Background: The number of deaths and illnesses caused by non-communicable diseases (NCDs) is increasing. One of the leading causes of NCDs is the behavior or patterns of people's daily habits. In the absence of a system that is used to detect NCDs with a behavioral approach, it is essential to research and create an application system for the early detection of NCDs.Purpose: This study aims to produce a system for the early detection of NCDs in pregnant women and provide recommendations based on an expert system.Method: This study employed Research & Development consisting of 4 stages, namely Literature Study, Development Stage, Validity Expert, and Trial.Results: This application has features that the public can use to detect NCDs independently. Users can perform early detection independently as needed; all user detection history data will be recorded in the detection history menu. In addition, users get health information through the health article menu. The results of trials conducted on pregnant women found that this application system was more effective than the manual. A mobile application can also increase the speed of diagnosis to 42%.Conclusion: This application is helpful for health workers and the public in conducting early detection of NCDs and providing education. This early detection application will make it easier for users to know their condition based on their behavior and make it easier for health workers to detect early and control the user's condition even from a distance.